Penerapan Model Induktif Kata Bergambar Dalam Meningkatkan Keterampilan Menulis Bahasa Indonesia Di Madrasah Ibtidaiyah - Kurniadi Abdurrahim (Al-Aulad: Journal of Islamic Primary Education, 2019)
This research was conducted to know Indonesia language writing skills of students before and after using the inductive model picture and words to find out its application in class II MI Nurul Huda Bandung. This research uses Research Action class that have been implemented over the last two cycles.  Based on the results of the data processing, the average value obtained the writing skills of students before using inductive model illustrated 60 words (30%).  Application of inductive model illustrated words on cycle I obtained average value of teacher activity 80.75% and students of 68.75% and cycle II obtained average value of teacher activity amounted to 96.15% and 93.75% students. Writing skills of the students after using inductive model illustrated words on cycle I gained an average rating of 74,5 (78%) and in cycle II obtained an average score of 81.6 (100%). This proves that the word inductive model illustrated is able to improve the writing skills of students in the class II MI Nurul Huda Bandung.